Pelatihan Pengelolaan Keuangan keluarga Bagi Ibu-Ibu Rumah Tangga Kelompok Wisma Anggrek Kelurahan Lapandan Kabupaten Tana Toraja - Dwibin Kannapadang; Westerini Lusdani; Althon K. Pongtuluran; Helba Rundupadang (Lembaga Pengembangan Kinerja Dosen, 2025)
The ability to manage family finances is a crucial aspect in realizing household economic resilience. In practice, many housewives do not have adequate knowledge and skills in budgeting, saving, and prioritizing needs wisely. This community service activity was carried out with the aim of improving family financial literacy among housewives, especially members of the Wisma Anggrek Group, Lapandan Village. The method of implementing the activity consists of three main approaches, namely counseling on basic family financial management materials, interactive discussions to explore participants' experiences and challenges, and simulations of realistic and applicable household budget preparation. The training material covers the basic principles of financial management, saving strategies, controlling expenses, and how to prioritize needs based on the scale of urgency and financial capabilities. The results of the activity showed a significant increase in participants' understanding of the concept of family financial management. Participants are able to draw up a simple budget, recognize unnecessary expenses, and start implementing consistent saving habits. In addition, group discussions encourage the creation of spaces for sharing experiences and practical solutions among participants, which strengthens the collective spirit in building healthy financial habits. This activity has a positive impact on shaping a more planned financial mindset and behavior among housewives. It is hoped that this training will be the first step in building sustainable household economic resilience, as well as encouraging family financial independence through wise and responsible financial management.